Istibdal Waqf Relevance on Development of Waqf in Indonesia - Hariyanto Hariyanto; Irham Zaki (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This study aims to describe madzhab Hambali’s perspective on waqf istibdal, in which there are many opinions among the scholars regarding the ability to implement istibdal on waqf goods. The differences of opinion among fiqh scholars in responding to the dynamics of waqf, the laws related to waqf and their management procedures are important to discuss, because they will have an impact on the formulation of policies that will be taken in the future. And discuss about waqf istibdal relevance on development of waqf in Indonesia by madzhab Hambali’s perspective. This research uses descriptive-qualitative research with the library research method. The results of this study indicate that waqf istibdal is allowed in the perspective of madzhab Hambali and it is very relevant to the development of waqf in Indonesia. Keywords: Waqf, Istibdāl, the Development, Madzhab Syafi’i.